2020
DOI: 10.1021/acschembio.0c00403
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Complex of Adenylation Domain and Carrier Protein by Using Pantetheine Cross-Linking Probe

Abstract: Adenylation domains (A-domains) are responsible for selective incorporation of carboxylic acid substrates in the biosynthesis of various natural products. Each A-domain must recognize a cognate carrier protein (CP) for functional substrate transfer. The transient interactions between an A-domain and CP have been investigated by using acyl vinylsulfonamide adenosine inhibitors as probes to determine the structures of several Adomain−CP complexes. However, this strategy requires a specific vinylsulfonamide inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…By engineering a Cys into the A domain active site via site-specific mutagenesis, Scheming and Tarry activated the A domain to make a disulfide bond with the PCP Ppant arm thiol (110), a linkage reminiscent of the disulfidebased cross-link between AcpP and FabF shown in Figure 4C. In another 'trapping' strategy that leverages mutagenesis, Miyanaga et al (111) showed that incorporating a Cys into the A domain active site and installing an electrophilic bromoacetamide pantetheine crosslinking probe on the PCP activates the PCP-A complex formation. Taken together, these approaches highlight additional flexibility in how type II PKS ACPs can potentially be stabilized in complex to other enzymes by altering the nucleophilicity and/or the electrophilicity of the component proteins and/or protein-bound substrates.…”
Section: Connections To Other Biosynthetic Pathways That Use Assembly Line Enzymologymentioning
confidence: 99%
“…By engineering a Cys into the A domain active site via site-specific mutagenesis, Scheming and Tarry activated the A domain to make a disulfide bond with the PCP Ppant arm thiol (110), a linkage reminiscent of the disulfidebased cross-link between AcpP and FabF shown in Figure 4C. In another 'trapping' strategy that leverages mutagenesis, Miyanaga et al (111) showed that incorporating a Cys into the A domain active site and installing an electrophilic bromoacetamide pantetheine crosslinking probe on the PCP activates the PCP-A complex formation. Taken together, these approaches highlight additional flexibility in how type II PKS ACPs can potentially be stabilized in complex to other enzymes by altering the nucleophilicity and/or the electrophilicity of the component proteins and/or protein-bound substrates.…”
Section: Connections To Other Biosynthetic Pathways That Use Assembly Line Enzymologymentioning
confidence: 99%
“…Initially, 150 mM of each pantetheineamide probe was mixed with 5 mM ATP, 7.5 mM MgCl 2 , 0.5 mM CoaA, 0.7 mM CoaD, 0.6 mM CoaE, 2.5 mM Sfp and 100 mM VinL in a buffer consisting of 50 mM NaH 2 PO 4 /K 2 HPO 4 pH 8.0 (total volume 25 ml). The VinL modification reaction was carried out at 301 K for 3 h. The conversion of apo VinL to modified VinL was confirmed by LC-ESI-MS analysis as described previously (Miyanaga et al, 2020). Next, the cross-linking reaction was initiated by adding 15 mM wild-type or mutant VinK directly into the reaction mixture.…”
Section: Cross-linking Reactionmentioning
confidence: 99%
“…Because we had previously synthesized bromoacetamide, chloroacetamide and trans-3-chloroacrylamide pantetheine probes (Fig. 2a), we enzymatically loaded these probes onto apo VinL in a one-pot reaction, as described previously (Miyanaga et al, 2020). The CoaA, CoaD and CoaE proteins from the CoA-biosynthetic pathway (Haushalter et al, 2008) were used for the conversion of each pantetheineamide to a CoA derivative, and the phosphopantetheinyl transferase Sfp (Quadri et al, 1998) was used to attach the phosphopanthetheineamide moiety of the resulting CoA derivative to Ser36 of apo VinL to generate each modified VinL protein.…”
Section: Cross-linking Reactionmentioning
confidence: 99%
“…Mechanism-based crosslinking probes have been used to probe protein-protein interactions in NRPSs. 19,20 Recently, Aldrich and co-workers utilized crosslinking probes to study the interactions between the PCP and C domains 19 and Eguchi and co-workers applied crosslinking probes to obtain structural information of PCP-A domain complexes. 20 Here we introduce the development of new crosslinking probes and their application with mutagenesis studies to investigate the NRPS E domain mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Recently, Aldrich and co-workers utilized crosslinking probes to study the interactions between the PCP and C domains 19 and Eguchi and co-workers applied crosslinking probes to obtain structural information of PCP-A domain complexes. 20 Here we introduce the development of new crosslinking probes and their application with mutagenesis studies to investigate the NRPS E domain mechanism. We had previously identified chlorovinylglycine, a mechanism-based inhibitor of alanine racemase, as a PCP and E domain crosslinker.…”
Section: Introductionmentioning
confidence: 99%